2009
DOI: 10.1021/nn900494s
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Molecular Dynamics Simulations of Dynamic Fullerene Self-Assembly in Benzene Combustion

Abstract: Using density-functional tight-binding (DFTB)-based quantum chemical molecular dynamics at 2500 and 3000 K, we have performed simulations of benzene combustion by gradually reducing the hydrogen to carbon (H/C) ratio. The accuracy of DFTB for these simulations was found to be on the order of 7-9 kcal/mol when compared to higher-level B3LYP and G3-like quantum chemical methods in extensive benchmark calculations. Ninety direct-dynamics trajectories were run for up to 225 ps simulation time, during which hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 59 publications
4
55
1
Order By: Relevance
“…We named the combination of dynamic GF self-assembly and cage shrinking the "shrinking hot giant" (SHG) road of fullerene formation. Our more recent QM/MD simulations [136,137] of combustion fullerene synthesis [114] confirmed that SHG applies also in the case where hydrocarbon fuels are burnt in an oxygen-lean environment. The presence of hydrogen was found to effectively delay ring condensation, which is stage (ii) described in Sect.…”
Section: The "Shrinking Hot Giant" Road Of Fullerene Formationsupporting
confidence: 63%
“…We named the combination of dynamic GF self-assembly and cage shrinking the "shrinking hot giant" (SHG) road of fullerene formation. Our more recent QM/MD simulations [136,137] of combustion fullerene synthesis [114] confirmed that SHG applies also in the case where hydrocarbon fuels are burnt in an oxygen-lean environment. The presence of hydrogen was found to effectively delay ring condensation, which is stage (ii) described in Sect.…”
Section: The "Shrinking Hot Giant" Road Of Fullerene Formationsupporting
confidence: 63%
“…It is envisaged that C 60 and C 70 then will form with high probabilities. 9,10 This combination of size-up and long-range, multistep, size-down fullerene formation is clearly different from earlier models in which C 60 and C 70 are assumed to be formed through size-up processes followed by fragmentation in few steps only. Here, we will discuss such formation scenarios-and various types of coalescence reactions in view of the intensities and kinetic energies of even-n C 70 + -C 180 + ions which we measure following 400 keV head-on Xe 20+ collisions with weakly bound ͓C 60 ͔ m clusters.…”
Section: Introductionmentioning
confidence: 72%
“…8 Recently Irle et al presented quantum chemical molecular dynamics simulations suggesting that hot giant fullerenes, C n with n Ͼ ϳ 90, self-assemble in hot carbon and hydrocarbon vapors. 9,10 In these calculations, the hot giant fullerenes ͑vibrationally highly excited and with distorted structures͒ shrink spontaneously to smaller fullerenes-mostly by C 2 -emissions far from thermal equilibrium. It is envisaged that C 60 and C 70 then will form with high probabilities.…”
Section: Introductionmentioning
confidence: 94%
“…Fig. 3 displays the ´calculated angle distribution for V 30 . As an illustration of the graphitization tendencies, note the emerging peak near 120° in the angle distribution function of the most stable vacancy cluster for n=30, chosen for illustrative purposes here.…”
Section: The Hypothesis Of "Graphitization" Tendencies In Vacancy Clumentioning
confidence: 99%